VANAME SHRIMP MARKETING STRATEGY AT PT DPP KAUR REGENCY - Yuristia, Rahmi; Asona, Henny Maria; Badrudin, Redy; Larasati, Mayang; Martina, Martina; Reflis, Reflis (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Cultivation of vaname shrimp ponds is conducted by PT. DPP exclusively, but many other companies are also involved in the vaname shrimp cultivation business center, which creates competition. To compete with other shrimp pond businesses, a marketing strategy is needed. The methods used are EFAS (External Factor Analysis Summary) and IFAS (Internal Factor Analysis Summary) analysis, SWOT analysis, and QSPM analysis. Based on the results of the SWOT matrix analysis, it is evident that the strategic position is in quadrant (I) where the strength factor is greater than the weakness factor and the opportunity factor is greater than the threat factor, thus indicating an aggressive strategy (Growth-Oriented Strategy). This means that PT DPP vannamei shrimp company is in a potential position, making it highly likely to continue doing business optimally. The prioritized alternative marketing strategies for vaname shrimp are: 1) maintaining good relations with consumers by fulfilling consumer orders according to demand, and 2) utilizing adequate facilities and infrastructure to maintain products in accordance with sales standards.